A Study on Leadership Strategies Used In Maharashtra Board Schools In Pune: Exploring Leadership Strategies in Maharashtra Board Schools: A Case Study in Pune (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Leadership From an organizational perspective is an art that influences people to attain an objective of an organization. Leadership does not belong to any one person.“Individual people do not posses leadership; leadership happens when people participate in collaborative forms of thoughts and action. Leadership Strategies and values are indispensable in all disciplines. Education, the process that makes a man complete is also an important field where leadership creates a great impact. This essay discusses in detail the leadership values adapted at schools with particular reference to Pune, India, and their impact on the students and the organization as a whole. Further, this report also gives a set of strategies to be adapted by board of management of schools in refining its in refining strategies and in order to improve the overall quality of education.